(3GdHYdHcjIs - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje bGd GdTjN GdEeGe GHf JjejI QVi Gddg Yfg aUd ai Cf GdbQBf cdGe Gddg djS TF efg cdGekG dZjQg dGLHQFjd hdG eMeO hdGZjQgeG bGd Gddg JYGdi (B( (3aEPG bQCJ GdbQBf aGSJYP HGddg ef GdTjWGf GdQLje s
(3BNQgG (B:s
(3hdgPG EVWQGH ajgG WQGFa ef CPcjGA GdfGS hfXGQge hGddg jgOi ef jTGA Edi UQGW eSJbje hGddg SHMGfg CYde HGdUhGH hGdMeO ddg GdcQje GdhgGH s
(3HdZJ ebGHdI hJUMjMGJ Ydi jO cGJHgGs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdMfHdjs